Rough fuzzy image analysis : foundations and methodologies - Pal, Sankar K.; Peters, James F. (Chapman & Hall/CRC mathematical and computational imaging sciences, 2010)
Fuzzy sets, near sets, and rough sets are useful and important stepping stones in a variety of approaches to image analysis. Emphasizing the utility of fuzzy, near, and rough sets in image analysis, this title introduces the fundamentals and applications in rough fuzzy image analysis